Single-cell heterogeneity of EGFR and CDK4 co-amplification is linked to immune infiltration in glioblastoma - Kacper A. Walentynowicz; Dalit Engelhardt; Simona Cristea; Shreya Yadav; Ugoma Onubogu; Roberto Salatino; Melanie Maerken; Cristina Vincentelli; Aashna Jhaveri; Jacob Geisberg; Thomas O. McDonald; Franziska Michor; et al. (Cell Reports, 2023)
Summary: Glioblastoma (GBM) is the most aggressive brain tumor, with a median survival of ∼15 months. Targeted approaches have not been successful in this tumor type due to the large extent of intratumor heterogeneity. Mosaic amplification of oncogenes suggests that multiple genetically distinct clones are present in each tumor. To uncover the relationships between genetically diverse subpopulations of GBM cells and their native tumor microenvironment, we employ highly multiplexed spatial protein profiling coupled with single-cell spatial mapping of fluorescence in situ hybridization (FISH) for EGFR, CDK4, and PDGFRA. Single-cell FISH analysis of a total of 35,843 single nuclei reveals that tumors in which amplifications of EGFR and CDK4 more frequently co-occur in the same cell exhibit higher infiltration of CD163+ immunosuppressive macrophages. Our results suggest that high-throughput assessment of genomic alterations at the single-cell level could provide a measure for predicting the immune state of GBM.